Mild coronary artery dilatation developed in some children with mild COVID‐19 but completely regressed within 3 months. (4th July 2022) - Rouva, Glykeria; Vergadi, Eleni; Hatzidaki, Eleftheria; Germanakis, Ioannis
Abstract: Aim: We studied the incidence and time course of any coronary artery changes in children up to 2 years of age who were hospitalised with mild COVID‐19. Methods: This was a single‐centre prospective study of 29 children (19 males) with a median age of 3 months and interquartile range (IQR) of 1.6–4.3 months. They were admitted to a Greek University hospital for mild COVID‐19 from 1 March to 30 December 2021. Three echocardiographic evaluations were performed at a median (IQR) of 19 (16–24) days, 82 (75–89) days and 172 (163–197) after the first symptoms. The prevalence of coronary artery dilation, regression, and changes was documented. Results: Coronary artery dilation was present in 3 (10.3%) cases at the first evaluation, with complete regression at the second. Regression was observed in 18/24 (75%) cases with follow‐up data and 9 (31%) demonstrated significant z‐score changes of >2. Coronary artery changes in any segment at any time were documented in 18/29 (62%) of the patients. Conclusion: Cases of transient and very mild coronary artery dilatation following mild COVID‐19 completely regressed within 3 months. Large‐scale studies are needed to document the extent and time course of coronary artery dilation following paediatric COVID‐19.